PERANAN PAK BERBASIS MULTIKULTURAL DALAM MENANGANI LONJAKAN KASUS HIV/AIDS : DI KALANGAN PELAJAR DAN MAHASISWA KOTA KUPANG - Apriliatus Laiskodat (Institut Agama Kristen Negeri Kupang, 2026)
Multicultural-based Christian Religious Education is a strategic approach in responding to the surge in HIV/AIDS cases among high school students and university students in Kupang City, which is influenced by low levels of reproductive health literacy, increasing risk-taking behaviors, uncontrolled exposure to digital media, and the complexity of cross-cultural interactions within a pluralistic society. The main challenges faced are not limited to medical aspects but also include weak character formation, minimal moral awareness, and the persistence of stigma and discrimination against People Living with HIV/AIDS in educational and social environments. This condition indicates a gap between religious value education and the social realities encountered by the younger generation. Using a qualitative–conceptual method based on theological, educational, and social literature review, this study aims to analyze the role of multicultural-based Christian Religious Education in building preventive awareness, dialogical attitudes, and contextual value transformation in addressing HIV/AIDS issues. Specifically, this research examines how PAK can strengthen moral resilience, shape an inclusive Christian identity, and cultivate empathy and social responsibility among learners. The multicultural approach emphasizes respect for diversity, rejection of stigma against PLWHA, reinforcement of cross-cultural solidarity, and empowerment of young people as agents of change in HIV/AIDS prevention efforts. By promoting a holistic educational model focused on early character formation, critical reflection, social responsibility, and continuous evaluation, this study affirms that multicultural-based Christian Religious Education is relevant and sustainable in shaping morally grounded, responsible learners who are committed to shared life within a pluralistic society.